Experimental and Investigational Pharmacotherapy for Psoriatic Arthritis: Drugs of the Future - Navarini L; Currado D; Costa L; Tasso M; Chimenti MS; Caso F (Dove Medical Press, 2020)
Luca Navarini,1,* Damiano Currado,1,* Luisa Costa,2 Marco Tasso,2 Maria Sole Chimenti,3 Francesco Caso2 1Unit of Rheumatology, Immunology and Clinical Medicine, Università Campus Bio-Medico Di Roma, Rome, Italy; 2Rheumatology Unit, Department of Clinical Medicine and Surgery, School of Medicine and Surgery, University of Naples Federico II, Naples, Italy; 3Rheumatology, Allergology and Clinical Immunology, Department of Systems Medicine, University of Rome Tor Vergata, Rome, Italy*These authors contributed equally to this workCorrespondence: Francesco CasoRheumatology Unit, Department of Clinical Medicine and Surgery, School of Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Naples 80131, ItalyTel +39 081 7463773Fax +39 081 5463445Email francescocaso1@yahoo.itAbstract: In recent years, different studies have shown in psoriatic arthritis (PsA), the pathogenetic role of multiple cytokines other than tumor necrosis factor-α, such as interleukin-17 (IL-17), and IL-23 and dysfunction of Janus kinase (JAK)-signal family pathway. These molecules also represent the target of recently developed biologic (bDMARDs) and targeted synthetic disease modifying antirheumatic drugs (DMARDs) (tsDMARDs) currently investigated in several Phase II and III randomized controlled trials (RCTs). This review examines the therapeutic efficacy and safety of most recent developed IL-17, IL-23 and JAK inhibitors and highlights how these new PsA therapies are going to revolutionize the management of PsA in the next few years. Ongoing RCTs of these molecules in PsA are also described. Available literature on new anti-IL-17 and anti-IL-23 agents and JAK inhibitors demonstrates the potential role of these molecules as effective therapeutic strategies across multiple PsA clinical domains, along with an acceptable tolerability and safety profile, thus expanding the treatment options available for PsA patients. Of note, other molecules are under investigation, and among those, potential therapeutic strategies seem to be represented by single antibodies blocking simultaneously two cytokines, the agents inhibiting mammalian target of rapamycin (mTOR), receptor retinoic acid receptor-related orphan receptor gamma (RORγt), A3 adenosine receptor (A3 AR), and K+ channel voltage channel inhibitors. Remarkable progress has been made in PsA pharmacotherapy, and novel bDMARDs targeting IL17A and tsDMARDs (JAK-inhibitors) represent promising therapies. More clinical trials are needed to better characterize the efficacy and safety profile of these therapeutic agents in PsA treatment.Keywords: bDMARDs, filgotinib, IL-17 inhibitors, IL-23 inhibitors, JAK-inhibitors, psoriatic arthritis, tofacitinib, tsDMARDs, upadacitinib